National STEM Education Framework: Teachers’ Perspectives on the 2015-2022 Curriculum Cycle - Kudakwashe Manokore; Lwazi Sibanda (Scientia Publica Media, 2024)
Throughout the world, nations are busy investing in Science, Technology, Engineering and Mathematics (STEM) to prepare innovative minds that can spearhead the development and sustainable growth of their economies. Zimbabwe’s participation in the global economy is premised on the preference for STEM education system. The introduction of the Competence-Based Curriculum (CBC) in Zimbabwe meant a shift in the general aims and objectives of the education system. The transformation meant a move from an academic oriented and content-focused curriculum to one that is skills-based, giving prominence to continuous assessment over final examinations. To explore classroom practitioners’ perceptions of the first cycle of the CBC, 20 purposively selected STEM teachers participated in the study. A qualitative research approach and case study design were adopted as study methodology. Thematically analysed data were collected through focus group interviews with participants. The study focused on support systems available for STEM education in secondary schools and how the absence of the national framework affects its implementation. The study found that there were limited support systems for STEM education as some schools did not have adequate facilities and equipment such as science laboratories, apparatus, science consumables, computer laboratories, computer hardware and software among others. It came out from the study that the absence of national framework had negative effect on the implementation of STEM education in secondary schools. The study concluded that though the secondary schools experienced constraints in implementing STEM education there were noticeable pockets of good practices in some schools, for example, learners graduating with competences for life skills. The study recommended that the schools should engage stakeholders for support in provision of required resources. The Ministry of Primary and Secondary Education should expedite the development of a national framework for the effective implementation of STEM education.